Determination of 8 Endogenous Alkaloid Components in Boletus Using Ultrahigh-Performance Liquid Chromatography Combined with Quadrupole-Time of Flight Mass Spectrometry - Junmei Ma; Qiang Li; Sufang Fan; Liangna He; Lei Sun; Di Wen; Hongwen Zhai; Yan Zhang (Journal of Food Quality)
A ultrahigh performance liquid chromatography coupled with quadrupole-time of flight mass spectrometry (UPLC-Q-TOF/MS) method was developed for simultaneous determination of 8 endogenous alkaloid compounds in Boletus. Boletus samples were extracted by 50% (V/V) methanol-water solution, then separated by CORTECS UPLC HILIC column using a binary solvent system by gradient elution. The analytes were determined by Q-TOF/MS in TOF MS and information dependent acquisition (IDA)-MS/MS mode. The results showed that mass accuracy error of the 8 endogenous alkaloids were lower than 5.0 × 10−6, good linear relationship was got in range of 0.2–500 μg/L, and correlation coefficient was higher than 0.9990. The limit of detection was in the range of 0.002–0.100 mg/kg and the limit of quantification was in the range of 0.004–0.200 mg/kg. Recovery of the method was in range of 80.1%–101.5% with spike levels of 0.004–2.00 mg/kg, relative standard deviations were lower than 10%. The method was simple, specific, and reliable. It could be used for the rapid screening and quantitative analysis of 8 endogenous alkaloids in Boletus.